Analysis of cognition structure of student’s having emotional, behavioral and learning difficulties: aspect of international experience - Radzevičienė, Liuda; Miliūnienė, Lina; Batūraitė, Aistė; Hoogerwerf, Evert-Jan; Charvatis, Adam; Bader, Michael; Oliv, Thomas; Grudeva, Petya (Social Welfare: Interdisciplinary Approach, 2019)
Article present international research on cognition, situation analysis of pupil who has emotional, behavioral and learning difficulties, that leads to early school drops. The main features of pupils who are not motivated in school attendance are problems in family environment and behavioral manifestations that lead to social conflicts. Method of deep-interview was applied during multifold individual meetings with pupil. Twenty-one student from four EU countries at the age from 13 to 20 years took part in the research. It was set that student’s difficulties and strengths at school, de-motivational and motivational aspects, weak points, problems of positive self-evaluation, coping strategies, helping thoughts, advice and wishes about future are the main inner psychological problems that reflects in student’s environmental acting.